International trade in food and agro-based products in the time of COVID-19 - Gombkötő, Nóra; Mezei, Katalin (Quaestiones Geographicae, 2024)
The aim of the study is to examine the regional impact of the COVID-19 pandemic and its individual waves on foreign trade in food and agro-based products in the world’s largest trading countries. The study was based on the statistical database of the International Trade Centre (ITC). In addition to the basic analysis, use was made of the auto- correlation method to detect special relationships between foreign food trade of different countries. The results show that the pandemic has had the greatest impact on agricultural and food trade in the United States, but it has spilled over to other countries as well, especially its two major trading partners, the European Union and China. Food trade stagnated in the initial period of the pandemic, but later recovered relatively well. The six examined regions can be divided into three groups based on the typical features of their autocorrelation.